2018
DOI: 10.1158/0008-5472.can-17-2676
|View full text |Cite
|
Sign up to set email alerts
|

R-spondin3 Is Associated with Basal-Progenitor Behavior in Normal and Tumor Mammary Cells

Abstract: R-spondin3 (RSPO3) is a member of a family of secreted proteins that enhance Wnt signaling pathways in diverse processes, including cancer. However, the role of RSPO3 in mammary gland and breast cancer development remains unclear. In this study, we show that RSPO3 is expressed in the basal stem cell-enriched compartment of normal mouse mammary glands but is absent from committed mature luminal cells in which exogenous RSPO3 impairs lactogenic differentiation. RSPO3 knockdown in basal-like mouse mammary tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Rspo3 is expressed in mouse MaSC‐enriched basal (Lin − CD24 + CD29 high ) epithelial populations, human basal ER − PR − cell lines, and human basal‐like tumors. Treatment of non‐tumor cells with recombinant Rspo3 induces EMT, whereas knockdown of Rspo3 in breast cancer cells induces mesenchymal‐epithelial transition (MET) with a reduction in cell migration capacity . Mechanically, Rspo3 controls EMT through modulating FZD ubiquitination by RNF43 and ZNRF3, thereby affecting the β‐catenin pathway triggered by Wnt ligands.…”
Section: Wnt Signaling Induces Breast Cancer Cell Epithelial‐mesenchymentioning
confidence: 99%
See 1 more Smart Citation
“…Rspo3 is expressed in mouse MaSC‐enriched basal (Lin − CD24 + CD29 high ) epithelial populations, human basal ER − PR − cell lines, and human basal‐like tumors. Treatment of non‐tumor cells with recombinant Rspo3 induces EMT, whereas knockdown of Rspo3 in breast cancer cells induces mesenchymal‐epithelial transition (MET) with a reduction in cell migration capacity . Mechanically, Rspo3 controls EMT through modulating FZD ubiquitination by RNF43 and ZNRF3, thereby affecting the β‐catenin pathway triggered by Wnt ligands.…”
Section: Wnt Signaling Induces Breast Cancer Cell Epithelial‐mesenchymentioning
confidence: 99%
“…Similarly, Rspo3 is not only secreted by mammary epithelial cells, but also by α-SMA-positive cells in breast cancer stroma. 62 It is reasonable to think that, similar to autocrine Rspo3, paracrine Rspo3 may also be involved in the activation of the Wnt/β-catenin pathway and in the induction of cancer cell EMT and stemness. It has been shown that myofibroblast-derived Rspo3 is required for the expression of Axin2 and Lgr5 in gastric epithelial stem cells.…”
Section: Epithelial -Stromal Crosstalk Of Breast Cancermentioning
confidence: 99%
“…Rspondin3 is expressed in normal basal and stromal cells. Its overexpression in breast cancers corresponds to high levels of a mesenchymal marker, whereas knockdown compromises lactogenic differentiation, xenograft growth, and lung metastasis (Tocci et al , ). There is currently active interest in developing neutralizing antibodies to various Rspondins (Chartier et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In breast tumors, RSPO2 and RSPO3 were first identified as being involved in BCa initiation, proliferation, epithelial-mesenchymal transition, and metastasis ( 53 ). The expression of RSPO2 and RSPO4 is increased in basal and metaplastic tumors ( 54 ), while the highest levels of RSPO3 expression were detected in basal BCa ( 55 ). We provide evidence that among the 4 members, only RSPO2 enhanced the recruitment of OPs, suggesting that the 4 members of the RSPO family have tissue-specific and spatiotemporally regulated functions in regulating cancer progression.…”
Section: Discussionmentioning
confidence: 99%